DAKWAH DIGITAL : PENDORONG PERUBAHAN SOSIAL DI MASYARAKAT MODERN - Novi Anggraeni; M. Rifki Hidayat; Nur Fitriyani; Qomariyah (Lembaga Sepercenter, 2025)
The development of technology brings social changes from various aspects, including in the religious realm, such as the method of preaching. The method of preaching that was previously carried out in the pulpit of the mosque or the majlis taklim, now preaching has spread to the digital platform. The public can easily see and listen to lectures anywhere and anytime. The purpose of this study is to describe digital preaching and social changes that occur in society. The research method used in this study is the library research method, namely a qualitative approach that utilizes various sources of literature as the main material in studying the phenomenon of digital preaching and its role in encouraging social change in modern society. The results of this study are that there are challenges and opportunities for digital preaching and the significant role of digital preaching in encouraging social change in modern society.